Bosnian phraseological units with a component-orientalism of the thematic group "Names of sweet dishes" - Irina V. Kuznetsova (Publishing house "Sreda", 2023)
The work is devoted to the analysis of Bosnian phraseological units with orientalism - the name of a sweet dish. The purpose of the article is to show the phraseological potential of borrowings-orientalisms naming sweets in the phraseology corpus of Bosnian Muslims. The relevance of the work is due to the need for a comprehensive study of phraseological units to identify common and idioethnic. The role of orientalisms in creating the imagery of phrasemes is shown in terms of ethnolinguoculturology. The material of the study is non-comparative phrasemes existing in Bosnia and Herzegovina. Methods of material processing: component analysis; linguoculturological analysis; structural and semantic modeling; comparative and synchronous descriptive. Structural and semantic models illustrate the interlanguage commonality of motivational ideas and at the same time specific, revealed at the level of imagery of phraseology. The research material shows a different phraseological potential of the names of sweet confectionery products of oriental origin. Arabisms and Persiisms as part of phraseological units are «indirect» borrowing: they entered of the inhabitants of Bosnia and Herzegovina through Turkish; they, like Ottomans, are more frequent in Bosnian phrasemes due to various historical and relevant reasons today. Some of the analyzed phrases are recorded by lexicographic sources and in other regions of Southern Slavia, but the activity of their use in live colloquial speech is typical precisely for the language of the inhabitants of Bosnia and Herzegovina, who have the so-called Bosnian Turkish.